MORPHOLOGY OF LYMPH NODES IN THE EXPERIMENT (AGE-RELATED AND CIRCANNUAL ASPECTS) - I. I. Markov; A. A. Krayushkin; N. G. Krayushkina; A. T. Yakovlev; E. A. Zagorodneva; E. V. Vlasova; N. I. Kovaleva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
In this experimental morphological study, we have obtained complex quantitative data reflecting different levels of the structural organization of normal lymph nodes in rabbits, with the consideration of their regional specificity, age, gender, time of day, specimen collection, and seasonal factors. We found that in mesenteric lymph nodes (MLNs) and inguinal lymph nodes (ILNs) of rabbits aged from 0 to 5 months, changes in the thickness of the capsule were insignificant. The relative area of the trabeculae in them increases, while the relative total area of the sinuses decreases. The reticuloarchitectonics of the node stroma becomes more complex by 3 months. There are no lymphoid nodules in the LNs of newborn rabbits; their number slightly increase by 5 months: in the autumn/winter season in MLNs and in the spring/summer season in ILNs. Regardless of LN locations and animal age, the ratio perimeter of the central section: number of lymphoid nodules was constant. From month 0 to month 5, the relative area of cortical plateau and Billroth's strands increases in MLNs and decreases in ILNs; the width of Billroth's strands increase in both MLNs and ILNs, while their relative area decreases in LNs of both locations. At the cellular level, we observed an increase in the number of small lymphocytes in the lymphoid nodules by month 5, a decrease in the proportion of blasts and large lymphocytes, an increase in the percentage of reticular cells and macrophages in both MLNs and ILNs. In the diffuse lymphatic tissue of the cortical substance of LNs, there was a decrease in the number of blasts and large lymphocytes and an increase in the number of macrophages. In the Billroth's strands, the percentage of reticular cells, large lymphocytes, and blasts decreases with age, while the number of small lymphocytes, plasma cells, and macrophages increases.